PERANCANGAN SISTEM INFORMASI PELAYANAN POSYANDU ANGGUR DEPOK - Mochammad Arief Sutisna; Triyanto (Jurnal Informatika Teknologi dan Sains, 2022)
Abstract: Today, the development of information technology is developing very rapidly. This is demonstrated by the many technologies that have the potential to impact the world of work and even the whole world, especially in the health sector. Accurate and reliable information is required to provide value to users of that information. There is no denying the urgent need for an information system for Posyandu and clinics. Information is important. Speed ??of information delivery and data access is equally important for organizations to remain competitive. With the rapid development of information technology, Depok Wine Poshandou always strives to innovate in information technology. One of the more advanced information technologies is the systems or applications that support the performance of Posyandu services. The currently running posyandu service system is still running manually. You have to contact the registry section. The registration section is time consuming as it has to summarize service data reports one by one. Make the running system less efficient in performing work activities. Based on current issues. So we need a system that allows the service to get information about posyandu's data. Applications are written using the PHP programming language and the MySQL database.